Comparative evaluation of the AES-Chemunex lab blender Smasher®, Seward Stomacher®, Interscience Bagmixer® and Pulsifier® on viable cell counts of foods, noise level, ergonomics, and ease of cleaning - Caballero Vidal, Cesar Guillermo (Kansas State University, 2009)
Proper microbiological examination of foods involves proper sample preparation in terms of mixing the solid or liquid food with a suitable sterile diluent (usually a 1:10 dilution) in a sterile bag and homogenizing them manually or by means of an instrument. This thesis addresses the effectiveness of Stomacher®, Pulsifier®, Bagmixer®, and Smasher® instruments in terms of: 1) Number of viable cell counts/g of ten food types, 2) Noise level of the four instruments ascertained by a) human and b) decibel meter at five feet (1.52 meters) from each instrument, 3) Ease in cleaning the instruments after use, and 4) Ergonomics. Following the ISO Method (7218:2007), 25 g each of alfalfa sprouts, spinach, peanuts, ground beef, fish meat, hot dogs, tofu, milk, chicken wing meat, and chicken drum stick meat were placed individually in a sterile sample bag containing 224.5 mL of 0.1% Peptone water plus 0.5 mL of E. coli inoculum diluent. Each food was homogenized for 60 seconds in each of the instruments. During each treatment four laboratory workers standing at five feet (1.52 meters) from the instrument assessed the noise level as: very quiet, quiet, nearly quiet, acceptable noise, and loud. Also the noise level was monitored instrumentally by the use of a decibel meter and recorded as Db. Ease of cleaning and ergonomics were determined with the aid of a subjective scale set with the Stomacher® as a reference point. The results indicate that all four instruments have similar performance in regards to viable cell counts. However, in regards to noise level, the Smasher® and the Bagmixer® are the quietest compared to the Stomacher® and then the Pulsifier®. The Smasher® is also the instrument with the highest ranking in ease of cleaning and ergonomics.
Keywords: Noise levels; Homogenizers; Biology, Microbiology (0410)